Ano internacional do esporte e educaçao física : o sistema onu e a pedagogia da hegemonia - Melo, Marcelo Paula de (2018)
International organizations have a relevant pedagogical role in the current capitalist society and the correlation of forces between social classes. The UN System (General Secretariat, its agencies and funds) play major role in this process. The set of issues that mark the neoliberal capitalist project focuses on the sports field and the UN system has to give a prominent role to sports. This resulted in the creation of a series of programs and actions. The substrate of these actions lies in the emergence of principles dear to the neoliberal project in this field
Os organismos internacionais cumprem relevante papel pedagógico no âmbito da atual fase da sociedade capitalista e na correlação de forças entre as classes sociais. O Sistema ONU (Secretaria Geral, suas agências e Fundos) ocupa papel de grande relevo nesse processo. O conjunto de questões que marcam o projeto capitalista neoliberal incide no campo dos esportes e o Sistema ONU passou a conferir um papel de destaque aos esportes. Isso implicou na criação de uma série de programas e ações. O substrato dessas ações radica na emergência de princípios caros ao projeto neoliberal nesse campo
Keywords: UN; Sports policies; Capitalism; ONU^lpt; Políticas de esportes; Capitalismo; Deporte; Capitalismo; ONU; Pedagogía